The Integration of Reason and Revelation in Addressing the Complexity of Contemporary Theology - Mukminin, Moh. Amiril; Amin, Nasihun; Mukit, Abdul (Journal of Islamic Thought and Philosophy, 2024)
This research focuses on the response of Ilmu Kalam to contemporary theological challenges, particularly related to atheism, secularism, and modern scientific developments. The underlying concern of this study is how Ilmu Kalam can maintain its relevance in addressing increasingly complex theological issues amidst the advancements in science and the dominance of atheistic views in contemporary academic circles. This study adopts a qualitative approach with a literature review of the thoughts of key figures in Ilmu Kalam, alongside critiques of atheism and secularism, to analyze how Ilmu Kalam responds to contemporary theological challenges. The main finding of this research indicates that Ilmu Kalam continues to transform by integrating reason and revelation to address contemporary theological challenges, although it still faces obstacles in innovating and critically responding to modern issues.